Understanding and designing head‐to‐tail cyclic peptides. Issue 10 (12th March 2018) - Slough, Diana P.; McHugh, Sean M.; Lin, Yu‐Shan
Abstract: Cyclic peptides (CPs) are an exciting class of molecules with a variety of applications. However, design strategies for CP therapeutics, for example, are generally limited by a poor understanding of their sequence–structure relationships. This knowledge gap often leads to a trial‐and‐error approach for designing CPs for a specific purpose, which is both costly and time‐consuming. Herein, we describe the current experimental and computational efforts in understanding and designing head‐to‐tail CPs along with their respective challenges. In addition, we provide several future directions in the field of computational CP design to improve its accuracy, efficiency and applicability. These advances, combined with experimental techniques, shall ultimately provide a better understanding of these interesting molecules and a reliable working platform to rationally design CPs with desired characteristics. Abstract :